Perancangan Sistem Informasi Absensi Siswa Berbasis Web Menggunakan Code QR/Barcode - Askar Saputra; Sahru Ramadhana; Nurul Awalya; Eriska Amalia Sakkar; Nurhinaya Nurhinaya; Sri Rejeki; Nurhalimah Nurhalimah; Sisil Damayanti; Muh. Alfarizki Asbir (Jurnal Teknologi dan Bisnis Cerdas, 2026)
The application of information technology in the field of education plays an important role in improving the effectiveness of academic data management, particularly in the student attendance process. Manual attendance systems that are still widely used in schools have several weaknesses, including a high risk of recording errors, low efficiency, and difficulties in processing and reporting attendance data. This study aims to design a web-based student attendance information system that supports fast, accurate, and integrated attendance recording. The research methodology includes requirements analysis, system design using Unified Modeling Language (UML), and the implementation of a web-based system with a centralized database. The developed system provides features for managing student data, teacher data, class schedules, attendance recording, and automatic report generation. The results of this study indicate that the web-based student attendance information system can improve teachers’ work efficiency and facilitate schools in monitoring student attendance in real time.